2000
DOI: 10.1046/j.1365-2648.2000.01558.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping after heart transplantation: a descriptive study of heart transplant recipients’ methods of coping

Abstract: The purpose of the study reported in this paper was to explore the coping strategies of heart transplant recipients. Using a qualitative research approach, interviews were conducted with 42 participants (35 men and seven women). Analysis of the data revealed eight coping strategies: acceptance/optimism, denial/avoidance, setting targets, comparing oneself with others, making attributions, seeking social support, having faith and changing priorities and perceptions. These are discussed in relation to the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Denial is the attempt to reject or avoid the reality of a stressful event. Denial has often been considered a negative emotional-focused coping style, and it may be fairly common among cardiac and heart transplant patients [38,39]. While denial has been associated with positive outcomes during short-term medical procedures [40] or during the early stages of a chronic stressful experience [41], it has been shown to be detrimental if it is prolonged, ostensibly because it prohibits individuals from engaging in more active coping efforts [20,41].…”
Section: Discussionmentioning
confidence: 99%
“…Denial is the attempt to reject or avoid the reality of a stressful event. Denial has often been considered a negative emotional-focused coping style, and it may be fairly common among cardiac and heart transplant patients [38,39]. While denial has been associated with positive outcomes during short-term medical procedures [40] or during the early stages of a chronic stressful experience [41], it has been shown to be detrimental if it is prolonged, ostensibly because it prohibits individuals from engaging in more active coping efforts [20,41].…”
Section: Discussionmentioning
confidence: 99%
“…More generally, prevention programmes can teach individuals to recognize and reduce sources of stress and help them to strengthen their personal competence, coping skills, and social resources. According to Kaba, Thompson, and Burnard (2000), interventions might focus on providing information to alert individuals to the demands they will confront and to potential coping strategies for managing them. Health professionals also might focus their efforts on mobilizing individuals' natural sources of support, as well as providing a caring, reassuring relationship with individuals themselves.…”
Section: Suggestions For Interventionsmentioning
confidence: 99%
“…Recently, researchers have suggested that the need to cope with the physical loss of a heart and acceptance of a donor heart may be antecedents to feelings of psychological distress (Kaba, Thompson, & Burnard, 2000) Several studies, most of which describe the practical experience with patients, deal with the problem of how patients cope with that strain. Rauch and Kneen (1989) described the patient's feeling of guilt about the donor's death.…”
mentioning
confidence: 98%
“…40 Three qualitative studies pointed out the importance of family and friends. [46][47][48] When support was sought and given, it gave the participants socially strengthened, but when friends disappeared when the support was needed it gave the recipients a feeling of a lost social life. 48 Stolf and Sadala 47 found that families had a central part in the process of social adaptation.…”
Section: Social Adaptationmentioning
confidence: 98%